Analisis Pajak Dalam Rangka Impor Dan Bea Masuk Pengadaan Pesawat Latih Dan Implikasinya Pada Mahalnya Biaya Pendidikan (Studi Komparatif Pada Politeknik Penerbangan Indonesia Curug, Ppic Dan Aero Flyer Institute) - Chairil Anwar Pohan; Aji Suryono; Notika Rahmi; Sunarmin Sunarmin; Agus Subagiyo (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2023)
The purpose of this study is to analyze the imposition of import taxes and import duties for training aircraft procurement and its implications for the high cost of education at Indonesian Aviation Polytechnic Curug and Aero Flyer Institute in 2017-2021. This study is a qualitative descriptive study with data collection techniques used are interviews, observations, and documents so that the researcher can draw conclusions.   The conclusion of import taxes imposition and import duties has a high influence in determining the high cost of flight schools. With the high cost of flight schools, it will affect people's interest in becoming a pilot. However, this is a burden that must be borne by the educational institution itself which in the end causes the high cost of pilot school to be charged to prospective pilot students. The imposition of import taxes includes Sales Tax on Luxury Goods, Income Tax and VAT because training aircraft are subject to these three tax components. These three components cause the high cost of pilot school.  In this case, the government must immediately review  the  taxation  policy  for  the procurement of training aircraft and educational institutions must also cooperate with various airline operator both at home and abroad to attract pilot graduates and this will increase the interest of the Indonesian people to become professional and reliable pilots.